Phylogeography of the Mountain Tapir (Tapirus pinchaque) and the Central American Tapir (Tapirus bairdii) and the Origins of the Three Latin-American Tapirs by Means of mtCyt-B Sequences - Ruiz-García, M.; Vásquez, C.; Pinedo-Castro, M.; Sandoval, S.; Castellanos, A.; Kaston, F.; Thoisy, B. de; Shostell, J. (IntechOpen, 2012)
None